Character Education Based on Local Wisdom Facing Global Economic Changes in The Decisions of Constitutional Court - et al., Sunny Ummul Firdaus (International Journal of Advanced Science and Technology, 2019)
Globalization continues to influence the character of everyone, and even tends to lose its character as a man of good character. This paper aims to explain that global change must be faced through character education based on local wisdom. In ensuring that education reaches its destination, the state must be present through all its instruments. This is because the advancement of character education will also determine competition in economics in the global arena. This research is a descriptive qualitative research because it uses the library research method. Data collection is done by collecting data in the form of writings that support this research. The results showed that the government’s efforts to implement character education were intended to build and strengthen character in schools. Schools as learning institutions instill values while creating human character. With the presence of the state through the understanding of the intellectual life of the nation which is supported by the emergence of the integrity of the organization of education in The Decision of the Constitutional Court Number 91/PUU-XIV/2016 can improve the quality of education itself. Whereas, the concept of character education based on local wisdom will teach values derived from the characteristics of local culture which will principally influence the character development of students in schools which can later develop and make national strength in the face of global competition.